2013
DOI: 10.1186/1746-6148-9-128
|View full text |Cite
|
Sign up to set email alerts
|

Corneal cross-linking in 9 horses with ulcerative keratitis

Abstract: BackgroundCorneal ulcers are one of the most common eye problems in the horse and can cause varying degrees of visual impairment. Secondary infection and protease activity causing melting of the corneal stroma are always concerns in patients with corneal ulcers. Corneal collagen cross-linking (CXL), induced by illumination of the corneal stroma with ultraviolet light (UVA) after instillation of riboflavin (vitamin B2) eye drops, introduces crosslinks which stabilize melting corneas, and has been used to succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 39 publications
2
44
0
5
Order By: Relevance
“…Calculations of ulcer area reduction per day revealed that wound healing progressed almost identically in both groups. The study thus indicates that CXL is probably not associated with adverse effects on wound healing rates in the horse cornea, which is in agreement with our previous study …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Calculations of ulcer area reduction per day revealed that wound healing progressed almost identically in both groups. The study thus indicates that CXL is probably not associated with adverse effects on wound healing rates in the horse cornea, which is in agreement with our previous study …”
Section: Discussionsupporting
confidence: 93%
“…CXL increases the bio‐mechanical strength and stabilizes the cornea by forming new cross‐links in the corneal stroma between collagen fibers and between proteoglycan core proteins, thus making it more resistant to melting and bacterial attack through steric hindrance . Hence, it has been used to treat corneal melting in humans, cats, dogs, and horses …”
Section: Introductionmentioning
confidence: 99%
“…Corneal cross‐linking has been described as treatment alternative for pellucid marginal degeneration in human patients and is a cost‐effective treatment modality that can be performed on a sedated standing horse, provided that the disease is detected early when corneal stromal loss is still limited . A minimum corneal thickness of 400 µm to allow sufficient absorption of the UV‐A radiation in the riboflavin saturated stroma is recommended to safely perform CXL and avoid endothelial, lens and retinal damage .…”
Section: Discussionmentioning
confidence: 99%
“…Eine neue und sehr interessante Behandlungsmöglichkeit, die ursprünglich zur Therapie des Keratokonus und aktuell auch gegen infektiöse Hornhautentzün-dungen eingesetzt wird, ist die CXL-Technik (corneal Collagen Crosslinking -CXL) [8,12]. Bisher wurden jedoch zu wenige Pferde mit dieser Technik behandelt, um die Ergebnisse objektiv beurteilen zu kön-nen.…”
Section: Chirurgische Therapieunclassified